Availability Of Inclusive City Park Infrastructure (Case Study: Taman Tirto Agung Semarang) - Khoirotun Hisan,; Wijayanti, (Jurnal Koridor, 2024)
City parks are places that support physical and social activities/discussions for all levels of society. Therefore, city park infrastructure needs to be accessible independently, even without the help of others. This research is located in Tirto Agung Park which is located in a mix-use area (education, housing, trade) so that park users come from various levels of society both in terms of age and competence. The method used in this study is qualitative with literature studies, and field observations were carried out to assess the availability and suitability of Tirto Agung Park infrastructure with the principles of universal design and the Regulation of the Minister of Public Works Number 14 of 2017 concerning Building Ease Requirements. The results of the analysis showed that Tirto Agung Park has shortcomings in providing facilities for users, especially people with disabilities, such as ramps (low physical effort), guiding blocks (simple and intuitive use), hand rails (equitable use), zebra crossings (tolerance for error) and wayfinding/signage (perceptible information). The recommendation in this study is to add, improve and maintain park facilities and infrastructure.